OpenWorm: overview and recent advances in integrative biological simulation of Caenorhabditis elegans. (10th September 2018) - Sarma, Gopal P.; Lee, Chee Wai; Portegys, Tom; Ghayoomie, Vahid; Jacobs, Travis; Alicea, Bradly; Cantarelli, Matteo; Currie, Michael; Gerkin, Richard C.; Gingell, Shane; Gleeson, Padraig; Gordon, Richard; et al.
Abstract : The adoption of powerful software tools and computational methods from the software industry by the scientific research community has resulted in a renewed interest in integrative, large-scale biological simulations. These typically involve the development of computational platforms to combine diverse, process-specific models into a coherent whole. The OpenWorm Foundation is an independent research organization working towards an integrative simulation of the nematode Caenorhabditis elegans, with the aim of providing a powerful new tool to understand how the organism's behaviour arises from its fundamental biology. In this perspective, we give an overview of the history and philosophy of OpenWorm, descriptions of the constituent sub-projects and corresponding open-science management practices, and discuss current achievements of the project and future directions. This article is part of a discussion meeting issue 'Connectome to behaviour: modelling C. elegans at cellular resolution'.